Up from clinical epidemiology & EBM - Miettinen, Olli S. (Olli Sakari) 1936-; SpringerLink (Online service). (Dordrecht London Springer, 2010)
Clinical epidemiology is now widely promoted and taught as a 'basic science' of evidence-based medicine, of clinical EBM to be specific. This book, however, is mostly about that which Miettinen takes to be the necessary substitute for this now-so-fashionable subject namely, Theory of Clinical Medicine together with its subordinate Theory of Clinical Research.The leit motif in all of this is Miettinen's perception of the need and opportunity to bring major improvements into clinical medicine in this Information Age, now that theoretical progress has made feasible the development of practice-guiding Expert Systems for it. Parts of this text constitute essential reading for whoever is expected, or otherwise inclined, to study--or teach--clinical epidemiology, and the same is true of those who set policy for the education of future clinicians; but practically all of it is essential reading for future--and current--academics in the various disciplines of clinical medicine. After all, the text is the result of a concentrated effort, over a half-century no less, to really understand both clinical and community medicine and the research to advance the knowledge-base of these. Research epidemiologists, too, will find this text interesting and instructive.
Electronic reproduction.
Keywords: Clinical epidemiology; Clinical medicine; Evidence-based medicine; Electronic books